2022
DOI: 10.1093/milmed/usac040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training Programs on Physical Fitness Domains in Military Personnel: A Systematic Review and Meta-Analysis

Abstract: Introduction Physical training is important to prepare soldiers for the intense occupational demands in the military. However, current physical training may not address all fitness domains crucial for optimizing physical readiness and reducing musculoskeletal injury. The effects of nontraditional military physical training on fitness domains have been inconsistently reported, which limits the design of the ideal training program for performance optimization and injury prevention in the milita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The arduous nature of the military service is well-known with soldiers expected to complete a range of occupational tasks [ 14 , 25 ]. Subsequently, physical training for the military must be extensive and robust to prepare the war fighter for both acute and chronic occupational physical demands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The arduous nature of the military service is well-known with soldiers expected to complete a range of occupational tasks [ 14 , 25 ]. Subsequently, physical training for the military must be extensive and robust to prepare the war fighter for both acute and chronic occupational physical demands.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this is a positive step in assessing the ability of personnel to perform essential occupational tasks, these assessments often provide limited insight into individual movement characteristics (e.g., symmetry) and opportunities to address injury risk factors [ 12 ]. Further, military personnel undertake a wide array of physical training including generic aerobic and strength activities, bodyweight training, functional fitness training, and strength training with free weights to enhance performance and minimise injury [ 13 , 14 ]. Whilst studies have confirmed that generic training improves the initial fitness of army personnel and may reduce MSKI risk [ 8 , 12 ], these practices do not target other MSKI risk factors such as balance and strength asymmetry [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marathon runs for a long time and consumes much energy. The performance of athletes is closely related to physical fitness 2 . Physical performance is also affected by the surrounding environment, including temperature, humidity, road slope, road friction, and so on 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%